2000
DOI: 10.1002/(sici)1521-3773(20000515)39:10<1826::aid-anie1826>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electronic Communication and Guest Inclusion Using Photoluminescent Macrocyclic Receptors with RuII Centers and Ph2P−C≡C−C≡C−PPh2 Spacers

Abstract: The study of photoluminescent and redox-active supramolecular systems has attracted recent attention as a consequence of a rapid growing interest in designing artificial arrays for applications in photonic and electronic devices. [1, 2] Systems with various designs have been studied using the assembly of active (for example, metal-based chromophores and redox-active moieties) and passive components (for example, rigid or flexible spacers) as a basis.[1±7] Such systems are constructed to gain a practical ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…8). 48 Electrochemical studies demonstrated the redox equivalence (i.e. insulation) of the metal ions in trimetallic complex 35, while two consecutive one-electron oxidations were seen for bimetallic complex 34, indicating communication between the two metal ions.…”
Section: Polymetallic Complexesmentioning
confidence: 98%
“…8). 48 Electrochemical studies demonstrated the redox equivalence (i.e. insulation) of the metal ions in trimetallic complex 35, while two consecutive one-electron oxidations were seen for bimetallic complex 34, indicating communication between the two metal ions.…”
Section: Polymetallic Complexesmentioning
confidence: 98%
“…Furthermore, these increases were dependent on both the charge and size of the anions, with higher charged or larger ions producing the biggest changes. 21 More recently the interaction of [17]Cl 4 with duplex DNA in water has been investigated. In these conditions it was found that the macrocycle binds to calf thymus-DNA with a high affinity (>10 6 M -1 ) resulting in a blue-shift and decrease in emission intensity.…”
Section: Self-assembled Optical Sensors 21 Octahedral Metal Ion Templ...mentioning
confidence: 99%
“…PPh 2 C 2 (C 6 H 4 ) n C 2 PPh 2 (n = 0 (L0), 1 (L1), 2 (L2), 3 (L3)) were prepared as previously reported. 19,20,25 Other reagents and solvents were used as received. The solution 1D 1 H, 31 P NMR and 1 H-1 H COSY spectra were recorded on a Bruker Avance 400 spectrometer.…”
Section: Introductionmentioning
confidence: 99%